Inequality, Justice, and the Myth of Unsituated Market Exchange. Issue 2 (30th May 2019) - Hicks, Douglas A.
Abstract: This article examines inequality from a framework of justice that attends to the socially situated nature of market activity, including exchange. I argue that accounts of unsituated exchange—accounts of market exchange that abstract from social situations, such as philosopher Robert Nozick's influential libertarian account of justice—overlook various factors that contribute to growing economic inequality in contemporary society. Analyses of market exchange must incorporate the role of "third parties" who play a role in shaping and/or who are affected by economic transactions. The involvement of these additional parties, including the government and future generations, is not interference but, instead, an integral part of the economic and moral accounting of exchange. An approach to justice and inequality which embeds exchange within multiple dimensions of economy and society is needed; the latter part of this article traces such a socially situated approach.